The benefits of augmented reality technology in higher education: a review of the literature - Wang, Dan; Md Khambari, Mas Nida; Wong, Su Luan; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Current development in Educational technology is changing traditional teaching approaches, making learning more interesting and effective. Today augmented reality (AR) technology is regarded as one of the frontiers in educational technology. Its utilization in teaching and learning has brought a revolution in the education sector. The researchers have explored the application of AR technology in different aspects of education. This research is aimed to answer the question: What are the benefits of AR technology at the tertiary education level? The systematic review and qualitative content analysis were utilized to answer the research question and the information gathered for this study are from empirical studies conducted in higher education. The findings of this study show that the application of AR technology in higher education is beneficial to college students’ learning performance and boost learning satisfaction and acceptance. Besides, the findings reveal AR technology has a significant effect on their learning motivation, interaction and collaborative learning. The results also point out that AR technology can reinforce content understanding. From the literature review, the researchers found that there are strong reasons to apply AR technology in university classroom. However, although AR technology has positive effect on learning in higher education, more research studies that are exploratory in nature need to be conducted in the future to get a deeper understanding of AR technology’s effects in several aspects of education.